Analysis of Financial Performance in Telecommunication Companies listed on the BEI - Nurul Iqza; Wa Ode Rayyani; Firman Syah (www.amertainstitute.com, 2023)
This study aims to analyze the financial performance of telecommunications companies listed on the Indonesian stock exchange in 2017-2021, by looking at financial reports using analytical tools, namely liquidity ratios, solvency ratios, activity ratios, and profitability ratios. This study uses descriptive and quantitative analysis methods, focusing on the company's financial performance. The type and source of data used are secondary data in the form of balance reports, income statements and the required data from 2017-2021, the data is taken from the telecommunications company's financial reports published on the Indonesia Stock Exchange. The company's sampling technique uses a purposive sampling technique. The analysis used is quantitative analysis consisting of liquidity ratios (current ratio, Quick ratio), solvency ratios (Debt to Asset Ratio, Debt to Equity Ratio), profitability ratios (Net Profit Margin, Return on Equity), activity ratios (Total Assets Turn Over, Inventory Turn Over)